Disruption of Traditional Grazing and Fire Regimes Shape the Fungal Endophyte Assemblages of the Tall-Grass Brachypodium rupestre - Durán, María; San Emeterio, Leticia; Múgica, Leire; Zabalgogeazcoa, Iñigo; Vázquez de Aldana, Beatriz R.; Canals, Rosa María (Frontiers in Microbiology, 2021)
The plant microbiome is likely to play a key role in the resilience of communities to the global climate change. This research analyses the culturable fungal mycobiota of Brachypodium rupestre across a sharp gradient of disturbance caused by an intense, anthropogenic fire regime. This factor has dramatic consequences for the community composition and diversity of high-altitude grasslands in the Pyrennees. Plants were sampled at six sites, and the fungal assemblages of shoots, rhizomes and roots were characterized by culture-dependent techniques. Compared to other co-occurring grasses, B. rupestre hosted a poorer mycobiome which consisted of many rare species and a few core species that differed between aerial and belowground tissues. Recurrent burnings did not affect the diversity of the endophyte assemblages, but the percentages of infection of two core species -Omnidemptus graminis and Lachnum sp. -increased significantly. The patterns observed might be explained by (1) the capacity to survive in belowground tissues during winter and rapidly spread to the shoots when the grass starts its spring growth (O. graminis), and (2) the location in belowground tissues and its resistance to stress (Lachnum sp.). Future work should address whether the enhanced taxa have a role in the expansive success of B. rupestre in these anthropized environments.